4-H Exploring Citizenship, Unit V: My Community - John Rutledge; Joy C. Jordan; Dale Pracht (EDIS)
The "My Community" project is an educational initiative designed to deepen understanding and involvement in one's local community. Addressing fundamental questions such as the nature of a community, the role of a citizen, available opportunities, and ways to foster community improvement, this project provides a comprehensive exploration into community dynamics. The project emphasizes experiential learning, encouraging participants to engage actively in their communities. Through this hands-on approach, participants will find the experience to be fun, exciting, challenging, and ultimately rewarding, fostering a greater sense of civic responsibility and community cohesion. This document was first time published in Oct. 1986